Tissue Insufficient for Diagnosis on Endometrial Biopsy: What's the Next Step? [1I]. (May 2016) - Gonzalez Rios, Angel R.; Chu Lam, Melissa T.; Shollenberger, Cori; Wagner, Jessica; Anasti, James
Abstract : INTRODUCTION: Endometrial biopsy (EMB) has been the gold standard for diagnosing causes of postmenopausal bleeding (PMB) for the last 30 yrs. Occasionally the EMB does not contain sufficient tissue to make a definitive diagnosis. This often leads to additional procedures. In an effort to improve the care of these patients, we evaluated PMB patients whose initial EMB did not contain sufficient tissue for diagnosis. METHODS: We reviewed EMBs done at our institution during a single year for PMB that were read as tissue insufficient for diagnosis (TIS). We collected demographics data, ultrasound data, and final pathology findings from a subsequent procedure (D&C or Hysterectomy) within 12 months of initial endometrial biopsy. RESULTS: There were 118 TIS results for 890 EMBs done for PMB (13.2%). The age, BMI, endometrial stripe and uterine sound were 61.2±9.1 years old, 31.3±8.5 kg/m 2, 7±4 mm and 7.6±1.7 cm (mean±SD), respectively. Of the 74 patients for whom we had additional tissue, 45 were atrophic (61%), 22 had endometrial polyps (30%), 6 proliferative (8%) and one endometrial cancer (1.3%). PMB patients with the two most common diagnoses (atrophy or polyps) did not differ in age, BMI, endometrial thickness, or uterine length. CONCLUSION: Insufficient tissue on EMB in PMB patients rarely results in serious endometrial pathology. The ability to differentiate between the two most common pathologies using ultrasound and demographics is difficult. Thus, the inclusion of a sonohysteroscopy may be helpful in determining the need for additional procedure.